2019
DOI: 10.1123/jsr.2017-0181
|View full text |Cite
|
Sign up to set email alerts
|

Field-Based Simplified Approach of Evaluating Knee Extensor Muscle Strength and Size in University Freshmen Women

Abstract: Context: Periodic assessment of knee extensor muscle strength and size is important for all ages to evaluate the functional status of individuals and to identify and treat those at risk for mobility problems and frailty; however, it is not fully understood whether these field-based simplified approaches correspond to evaluation in knee extensor muscle strength or size. Objective: To examine the relationship between field-based simplified evaluation approaches and knee extensor muscle strength or size in young … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…The maximum value of measurements was selected for analysis. According to the results of previous studies, KES was positively correlated with HGS ( r =0.380, p <0.01) [ 21 ]. Thus, we calculated HGS using the following formula: HGS = (KES − 15.1)/0.65.…”
Section: Methodsmentioning
confidence: 73%
“…The maximum value of measurements was selected for analysis. According to the results of previous studies, KES was positively correlated with HGS ( r =0.380, p <0.01) [ 21 ]. Thus, we calculated HGS using the following formula: HGS = (KES − 15.1)/0.65.…”
Section: Methodsmentioning
confidence: 73%
“…In addition, some studies reported that muscle morphology (thigh girth or MTH) was significantly correlated with muscle strength (handgrip or knee extension) and skeletal muscle mass (lean body mass) in young/middle-aged adults. [20][21][22] Therefore, we hypothesized that thigh muscle morphology rather than calf muscle morphology would be a useful indicator in evaluating skeletal muscle mass and maximum muscle strength. The purpose of this study was to examine the prediction of skeletal muscle mass and maximum muscle strength using simplified morphology evaluation in young Japanese women from the thigh and calf perspective.…”
Section: Introductionmentioning
confidence: 99%